Satisfaction and frustration of basic psychological needs in the real world and in video games predict internet gaming disorder scores and well-being. (July 2018) - Allen, Johnie J.; Anderson, Craig A.
Abstract: The need-density hypothesis proposes that pathological gaming is most likely to occur when satisfaction of three basic human needs (competence, autonomy, relatedness) is low in the real world but high in video games. Our study tested this hypothesis to determine whether real-world need satisfaction and video game need satisfaction independently predict internet gaming disorder scores (IGD). We also assessed the effects of need frustration in both domains. As expected, we found strong support for the need-density hypothesis in terms of need satisfaction. Unexpectedly, need frustration in both domains was positively associated with IGD scores. A second goal of our study was to determine how the satisfaction and frustration of needs in both domains relate to well-being. We found consistent associations between well-being and real-world need satisfaction and frustration. Associations between well-being and video game need satisfaction and frustration were inconsistent, however. This pattern suggests that the satisfaction and frustration of needs in the real world is more important for well-being than the satisfaction and frustration of needs in video games. Thus, the real-world superiority hypothesis was supported over the video game superiority and equivalence hypotheses. Highlights: IGD was highest when need satisfaction was low in the real world but high in games. Need frustration in the real world and video games positively predicted IGD scores. Real-world need satisfaction and frustration consistently predicted well-being. Video game need satisfaction and frustration inconsistently predicted well-being.